ANALISIS GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA PENDIDIK SMK NEGERI 1 PALASAH KABUPATEN MAJALENGKA - Cucu Sunarti (Universitas Majalengka, 2021)
The research aims to analyze and find out: a) the leadership style of the principal; b) The achievement of the principal in improving the performance of educators; c) Supporting factors and inhibiting leadership style; d) The efforts of the principal in overcoming obstacles. The study used a qualitative approach, techniques and primary data collection tools using in-depth interviews with selected informants purposively. Data were analyzed descriptively interpretive through data reduction, data presentation, and drawing conclusions. The validity of the data was tested through triangulation techniques. The results showed: a) The principal's leadership style is dominant in the type of coaching (training): b) The principal's achievements in improving the performance of educators include professionalism, creativity, discipline and awareness as well as interest in writing scientific papers; c) Supporting factors have some young and productive teachers, many opportunities for teachers to develop themselves. Inhibiting factors include limited costs, low interest of educators in writing scientific works, and technical barriers; d) The principal has done well in overcoming the obstacles he is facing. In conclusion, the leadership style of the principal is dominant in the type of coaching and is able to improve teacher performance